A COLLECTIVE MEMORY OF A CITY IRIS CULTURAL CENTER IN ELEUSINA - Bouras, Constantine (Design/Arts/Culture, 2020)
The project is about the conversion of two listed buildings of the former paint factory IRIS in Eleusina into a multipurpose cultural center. Like all abandoned industrial relics in the area, the two listed buildings manifest strong ties with the industrial past of Eleusina and the collective memory of its inhabitants. The repurposing of the buildings by architect Constantine Bouras produces a space for theater, cinema, music, congresses, art exhibitions and other cultural activities, while part of it is home to the Aeschylus Museum.